2002
DOI: 10.1093/carcin/23.8.1351
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyclooxygenase-2 (COX-2) in two different morphological stages of intestinal polyps in APCΔ474 knockout mice

Abstract: The expression of COX-2 participates strongly in polyp formation of adenomatous polyposis coli (APC)-mutated mice. However, the mechanism of growth inhibition by COX-2 inhibition remains unclear. The aims of this study were to assess the role of COX-2 during the process of polyp formation in APC(Delta474) knockout mice. Starting at 4 weeks of age, the treated group (T group) were given a diet containing JTE-522, a selective COX-2 inhibitor, and the control group (C group) were given a control diet. At 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…The increased expression of COX-2 in MDF is mostly due to stromal cells. Accordingly, we also found that macrophages (CD-68 positive cells) were present in the stroma pertaining to MDF, suggesting, as reported by others, 25,37,38 that these cells could contribute to COX-2 activity during colon carcinogenesis. Macrophage infiltration higher than that in normal mucosa was also found in tumours, but not in ACF.…”
Section: Discussionsupporting
confidence: 88%
“…The increased expression of COX-2 in MDF is mostly due to stromal cells. Accordingly, we also found that macrophages (CD-68 positive cells) were present in the stroma pertaining to MDF, suggesting, as reported by others, 25,37,38 that these cells could contribute to COX-2 activity during colon carcinogenesis. Macrophage infiltration higher than that in normal mucosa was also found in tumours, but not in ACF.…”
Section: Discussionsupporting
confidence: 88%
“…Comparing systemic VEGF-A inhibition by Mab G6-31 to genetic deletion of VEGF-A in the intestinal epithelial compartment suggests that, in addition to epithelial cells, other cellular sources of VEGF-A play an important role in Apc ϩ/min adenoma growth. These additional sources of VEGF-A potentially include mononuclear cells (34) and stromal fibroblasts (35,36). Our in situ analysis indicates extraepithelial VEGF-A expression within the adenomas and normal villi, supporting this notion.…”
Section: Discussionsupporting
confidence: 78%
“…14,15 This compound also inhibited liver and lung metastases of colon cancer expressing COX-2 but lacked effect on those lacking COX-2 expression in the nude mouse xenograft model. 16,17 In chemically induced colon carcinogenesis, we have previously shown that JTE-522 inhibited the development of aberrant crypt foci (ACF), the putative precursors of both human and experimental colon cancer, 18,19 when administered throughout the study.…”
mentioning
confidence: 99%